Optical biosensor: approach, challenges and future - Mohd Salleh, Mohd Hazimin (2015)
In this presentation, full potential of optical waveguide such as Bragg grating polymer as a biosensor will be discussed. Visible wavelength region at 650 nm is used as centre wavelength because it is commonly used in biological and chemical sensing for both label or label-free sensing. Updates upon progress and future work in IIUM Kuantan also presented during this session.